Observations on Nematode Populations of Undisturbed Fynbos Compared with Those in an Adjacent Vineyard and a Pine Plantation - Meyer, A.J. (South African Journal of Enology and Viticulture, 2025)
The nematode species present in natural fynbos, represented by Protea repens were examined qualitatively and quantitatively and compared with those occurring in an adjacent vineyard and pine plantation. The latter maintained very low numbers of few species of free-living and plant parasitic nematodes when compared with the fynbos community. In contrast, the vineyard maintained the highest numbers of plant parasites, but fewer species of predatory and free-living nematodes. The fynbos, which can be regarded as the original habitat, had the greatest bio-diversity, but the plant parasitic species never reached the high numbers they attained in the rhizosphere of